(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article offers a model of learning research and its application in distance education. The questions of the characteristics of the perception of the educational process by students with different types of interaction of thinking and practical activity are considered. The authors analyze the stages of the educational process in accordance with D. Kolb’s theory and consider the specifics of their application in distance education. The learning process in a professional environment is complex, and the result is influenced by many factors. Learning styles and learning strategies have a significant impact on the effectiveness and quality of learning, regardless of whether we are aware of these concepts or not. Therefore, it is better to have an idea about them so that we can consciously use this information to build effective online learning. The use of this method will facilitate the process of distance education and improve the quality of education.